NI‐0801, an anti‐chemokine (C‐X‐C motif) ligand 10 antibody, in patients with primary biliary cholangitis and an incomplete response to ursodeoxycholic acid. Issue 5 (23rd March 2018) - de Graaf, Kathy L.; Lapeyre, Geneviève; Guilhot, Florence; Ferlin, Walter; Curbishley, Stuart M.; Carbone, Marco; Richardson, Paul; Moreea, Sulleman; McCune, C. Anne; Ryder, Stephen D.; Chapman, Roger W.; Floreani, Annarosa; et al.
Abstract : In primary biliary cholangitis (PBC), damage to the liver is caused by lymphocytes that enter the liver from the blood and then become activated to attack and destroy the bile ducts; CXCL10, a chemotactic protein, is particularly important in this migratory process. Therapeutic benefit of NI‐0801, an anti‐CXCL10 antibody, could not be demonstrated in PBC patients with an incomplete response to UDCA. Pharmacokinetics/ pharmacodynamics analysis as well as functional work‐up, including the use of an 'ex vivo' chemotaxis assay, suggest that target neutralization in the tissue might not have been achieved, resulting in the failure of this immunomodulatory treatment. Abstract : NI‐0801 is a fully human monoclonal antibody against chemokine (C‐X‐C motif) ligand 10 (CXCL10), which is involved in the recruitment of inflammatory T cells into the liver. The safety and efficacy of NI‐0801 was assessed in patients with primary biliary cholangitis. In this open‐label phase 2a study, patients with primary biliary cholangitis with an inadequate response to ursodeoxycholic acid received six consecutive intravenous administrations of NI‐0801 (10 mg/kg) every 2 weeks. Patients were followed up for 3 months after the last infusion. Liver function tests, safety assessments, as well as pharmacokinetic and pharmacodynamic parameters were evaluated at different time points throughout the dosing period and the safety follow‐up period. Twenty‐nine patients were enrolled in the study and were treated with NI‐0801. The most frequently reported adverse events included headaches (52%), pruritus (34%), fatigue (24%), and diarrhea (21%). No study drug‐related serious adverse events were reported. NI‐0801 administration did not lead to a significant reduction in any of the liver function tests assessed at the end of the treatment period (i.e., 2 weeks after final NI‐0801 administration) compared to baseline. Conclusion: Despite clear pharmacologic responses in the blood, no therapeutic benefit of multiple administrations of NI‐0801 could be demonstrated. The high production rate of CXCL10 makes it difficult to achieve drug levels that lead to sustained neutralization of the chemokine, thus limiting its targetability. ( Hepatology Communications 2018;2:492‐503)